THE LIQUIDATOR LIABILITY IN THE PROCESS OF CORPORATE LIQUIDATION - Agus Nurudin (Fakultas Hukum, Universitas Diponegoro, 2019)
Provisions of Article 149 paragraph (1) of Law Number 40 of 2007 concerning Limited Company/Limited Liability Company do not mention the authority to verify bill of creditors and the authority to sell property assets. In practice, the liquidator often acts as the seller of the company’s assets. This was doneto fill the legal vacuumfor the smooth liability of the liquidator. Therefore, the problem is how are the provisions of the legislation to the obligations of the liquidator in the process of liquidation of the limited liability company? The study approach method used is a description of juridical ciritical analysis. The urgency of writing this article is so that the liquidator is authorized to verify creditor bills and authority and sell assest. The result of a descriptive study of critical analysis are normal obligations of the liquidator to do the liquidation of the company’sassest other than those stipulated in article 149 paragraph (1) namely the authority to verify the creditor’s bill as well as the authority to sell Limited Liability Company assets.